Cathodoluminescence properties of oxide and fluoride ceramics synthesized in the field of high-energy electrons flux; Вестник Карагандинского университета. Серия Физика; № 4 (116) - Karnaukhova A. A. Anna Alekseevna (2024, 2024)
Traditionally, the synthesis of refractory ceramics is a complex and time-consuming process. Some time ago, a new, much faster method was proposed — the method of synthesis of luminescent ceramics in the field of a powerful flux of high-energy electrons. In the synthesis of multicomponent oxide phosphors, it is not an easy task to determine the dependencies of the properties of the resulting material on the composition of the raw mixture and the modes of the synthesis process. In this regard, it seems logical to study the properties of ce- ramics made by radiation synthesis from simple oxides, which are components of more complex phosphors. An investigation of the spectral and kinetic patterns of cathodoluminescence of ceramic samples of metal ox- ides (Ga2O3, Al2O3, Y2O3) and fluorides (MgF2, BaF2) obtained by radiation synthesis method was carried out. The paper presents an analysis of the cathodoluminescence spectra of the studied samples with the allo- cation of elementary bands, conclusions about the dynamics of luminescence decay are made. The obtained results are compared with the known data on single crystal samples. It is shown that, unlike oxide ceramics, the spectral characteristics of MgF2 and BaF2 ceramic samples show good agreement with the data on single crystals of these compounds